2014
DOI: 10.1007/s40089-014-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of physicochemical parameters on the synthesis of silver nanowires via polyol method

Abstract: The potential applications of one-dimensional nanostructured materials widely depend on their shape and size. This paper deals with a method for synthesizing and characterizing silver nanowires through an organic solution. The so-called polyol method was used to synthesize silver nanowires in which ethylene glycol was used as both media and the reducing agent. Adequate CuCl 2 /ethylene glycol solution is used to prohibit chemical etching by the oxygen on nanowires surfaces. The effects of CuCl 2 concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several authors have reported peaks of absorption spectra of AgNPs in the range 391-440 nm [10,11,[34][35][36][37], while the peak at 292 nm could be attributed to the presence of proteins [38]. However, plasmon resonances for the transverse and longitudinal plasmon bands at 350 and 390 nm, respectively, typified of anisotropic metallic onedimensional nanostructures have been reported [39].…”
Section: Biosynthesis and Characterisation Of Silver Nanoparticlesmentioning
confidence: 99%
“…Several authors have reported peaks of absorption spectra of AgNPs in the range 391-440 nm [10,11,[34][35][36][37], while the peak at 292 nm could be attributed to the presence of proteins [38]. However, plasmon resonances for the transverse and longitudinal plasmon bands at 350 and 390 nm, respectively, typified of anisotropic metallic onedimensional nanostructures have been reported [39].…”
Section: Biosynthesis and Characterisation Of Silver Nanoparticlesmentioning
confidence: 99%
“…The optical absorption as a function of wavelength is the simplest way to study the size dependent optical properties of the material [13,14]. Figure 5 shows the absorption spectrum of Mn-doped ZnS nanoparticles.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Typically, this method is performed by reducing silver salts or silver oxides with polyols, crystal seeds (e.g., platinum), and reducing agents (primarily ethylene glycol (EG)). [64][65][66][67][68][69] This method facilitates spontaneous separation between the crystal seed and AgNWs after nucleation. The factors affecting the quality of AgNWs synthesized via the polyol method include the molecular weight and concentration of capping agents (e.g., polyvinyl pyrrolidone (PVP) and hexadecyl trimethyl ammonium bromide (CTAB)), the type and concentration of the controlling agents (e.g., FeCl 3 , CuCl 2 , NaCl, or NaBr), stirring speed, reaction temperature, and time.…”
Section: Preparation Of Agnwsmentioning
confidence: 99%